Nautical tourism affects common bottlenose dolphin (Tursiops truncatus M.) foraging success in a NATURA 2000 site, North-Eastern Adriatic Sea - RIBARIC, DARJA; CLARKSON, JACK (Mediterranean Marine Science, 2021)
Several studies indicate that unregulated nautical tourism can have negative implications on cetacean behaviour. In recent years, dolphin watching activities (DWA) have increased off the West coast of Istria, Croatia, a region in which the NATURA 2000 site: ‘Akvatorij zapadne Istre’ has been proposed to be designated for bottlenose dolphins (Tursiops truncatus M.). For data collected between 2016 and 2019, we compared dolphin group behaviours from this region during impact (presence of nautical tourism boats (NTBs)) and control (absence of NTBs) scenarios, as well as providing descriptive analysis on the displacement of individuals in the presence of NTBs. Throughout the study years, 48.5 % of NTBs were observed within 15m of the dolphin focal groups and 97 % were observed within 50 m distance. The greatest rates of displacement in dolphin focal groups occurred when NTB numbers were greatest per individual dolphin. Markov chain analysis were used to quantify the short-term effects of NTB presence on dolphin behaviour. In the presence of NTBs, dolphins were more likely to spend time milling and less time foraging. Cumulative behavioural budgets, derived by accounting for the time bottlenose dolphins spent in the presence or absence of NTBs, indicated that vessel exposure levels of 14 % and 25 % were enough to statistically affect milling and foraging behaviours respectively. To lessen the lack of sustainable DWA, the implementation of relevant guidelines, e.g. Global Best Practice Guidance for Responsible Whale and Dolphin Watching (50 m no approach and 300 m caution zone) is therefore crucial to mitigate any long-term consequences the actions of NTBs may have on this key species. To date, 162 bottlenose dolphins have been photo-identified off West coast of Istria and cumulative interference to this population could affect direct ecosystem functioning.